Przestrzenne zróżnicowanie oferty edukacyjnej na Dolnym Śląsku na tle sytuacji demograficznej - Błaczkowska, Anna (Spatial disparities in educational offer in Lower Silesia based on demographic situation, 2008)
The aim of this article is to apply some methods of spatial market analysis to assess the degree of availability of post junior secondary school. The paper presents how the demographical situation in Lower Silesia will change in 2010 in relation to the year 2006. In the next step, allocation and concentration of high schools and universities in Lower Silesia in comparison to demographical situation have been discussed. Florence location ratio and Lorenz coefficient of concentration have been calculated. Reilly’s Law of Retail Gravitation has been used for determination of meaning and coverage of interaction of educational centres.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 115-126